The Urgency of Restorative Justice Implementation in Addressing Domestic Violence Cases to Realize Justice Oriented towards Victim Recovery - Agus Supriyanto; Abdullah Sulaiman (Jurnal Indonesia Sosial Teknologi, 2025)
The study is to examine, from the standpoint of legal advantages, the regulation and application of restorative justice in addressing domestic violence (DV) cases. In order to achieve a fair and beneficial conclusion, restorative justice places a strong emphasis on victim recovery, offender accountability, and community involvement. This study examines laws that support the implementation of restorative justice, such as Police Regulation Number 8 of 2021 and Prosecutor's Regulation Number 15 of 2020, and their applicability to the protection of domestic violence victims using a normative legal method that combines a statute approach and a conceptual approach. The study's findings suggest that a different approach to DV case resolution may be restorative justice, especially in ongoing social relationships, such as husband-wife or parent-child, so that it can reduce the negative impact of conventional criminalization on families, including social and economic aspects. However, its application must be carried out selectively, considering the risk of pressure on victims to reconcile and the potential for the recurrence of violence. From the perspective of legal benefits, restorative justice implementation can provide broader benefits compared to the retributive punishment system, provided that there is strict supervision and a mechanism that ensures that justice for victims remains a top priority. Therefore, evaluation and strengthening of regulations are needed to ensure that the implementation of restorative justice in domestic violence cases truly provides legal protection and benefits for all parties involved.